Susceptibility to and severity of tuberculosis infection in mice depends upon MHC-II-determined level of activation-inhibition balance in CD4 T-cells - Logunova, Nadezhda; Kapina, Marina; Kriukova, Valeriia; Britanova, Olga; Majorov, Konstantin; Linge, Irina; Apt, Alexander (Frontiers in Immunology, 2025)
Previously we have shown that H2-congenic recombinant mice of the B6.I-9.3 (H2-Ab1j) strain are significantly more susceptible to tuberculosis (TB) infection compared to their C57BL/6 (B6, H2-Ab) ancestors. Impaired TB control was characterized by decreased selection and maintenance of CD4+ T-cells, their profoundly narrower TCR repertoires, and a disproportionally enlarged neutrophil population. All phenotypes were expressed before TB infection, thus reflecting the steady state of the immune system and providing the basis of true genetic TB susceptibility. We anticipated that the differences in parameters of pre-infection immune homeostasis would seriously influence development of specific immune responses shortly after mycobacterial invasion and affect TB defense thereafter. In this study, we report on the dynamic phenotypes of CD4+ T-cells responding to infection which differ profoundly between mice bearing different MHC-II alleles. First, during post-challenge week 3, despite identical lung mycobacterial load, mice carrying the “resistant” H2-Ab allele recruited significantly more mycobacteria-specific, IFN-γ-producing CD4+ T-cells to their lungs compared to H2-Ab1j allele carriers. Second, during a few months post challenge, B6 mice were able to control both the size of the IFN-γ-producing CD4+ T-cell population and the total proportion of activated CD4+ T-cells at levels significantly lower than those in B6.I-9.3 mice. Finally, in TB-susceptible mice, a higher proportion of CD4+ T-cells expressed both activation-associated and immune inhibition (checkpoint) markers, accompanied by functional CD4+ T-cell exhaustion at late stages of infection. Together, these observations suggest that suboptimal pre-infection MHC-II-dependent shifts in immune homeostasis affect both early and late immune reactions against TB.